The Nine Hour Pioneers: The Genesis of the Canadian Labour Movement - Battye, John (Labour / Le Travail, 1979)
This paper documents the attempt to obtain the nine-hour working day in Canada during the first six months of 1872. The primary role of the working class of Hamilton and Montreal is indicated and the view is taken that the Toronto Printers' Strike obscured, rather than advanced, the aims of the nine-hour movement. It is argued that, while there was certainly developing a class identity and a trade union consciousness, there existed only an inchoate sense of class consciousness among Canadian workers during the early 1870s.

The Labour Movement in Latin America: A Review Essay - Blanchard, Peter (Labour / Le Travail, 1979)
The article reviews and comments on "Outcasts in Their Own Land: Mexican Industrial Workers, 1906-1911," by Rodney D. Anderson, "Chilean Rural Society from the Spanish Conquest to 1930," by Arnold J. Bauer, "Land and Labour in Latin America: Essays on the Development of Agrarian Capitalism in the Nineteenth and Twentieth Centuries," edited by Kenneth Duncan and Ian Rutledge, with the collaboration of Colin Harding, "The Brazilian Corporative State and Working-Class Politics," by Kenneth Paul Erickson, "Anarchism and the Mexican Working Class, 1860-1931," by John M. Hart, "A History of the Bolivian Labour Movement 1848-1971," by Guillermo Lora, edited and abridged by Laurence Whitehead, "Labor and the Ambivalent Revolutionaries: Mexico, 1911-1923, by Ramon Eduardo Ruiz, "Struggle in the Countryside: Politics and Rural Labor in Chile, 1919-1973," by Brian Loveman, " Organized Labor in Latin America: Historical Case Studies of Workers in Dependent Societies," by Hobart A. Spalding, Jr.

The Great Tribulation: Winnipeg's First General Strike - Brammel, Libertas; McCormack, A. Ross (Labour / Le Travail, 1979)
Published in Winnipeg in 1902 under the pseudonym of Libertas Brammel, the futuristic novelette, "The Great Tribulation," was a harbinger of the Winnipeg General Strike of 1919. Set in Winnipeg in 1960, "The Great Tribulation" chronicles a society with deep class tensions that culminate in "the greatest strike ever known." A. Ross McCormack introduces this abridged version, which originally appeared in the labour publication, "The Voice."

Work Without Salvation: America's Intellectuals and Industrial Alienation, 1880-1910 ; The Work Ethic in Industrial America 1850-1920 - Cook, Ramsay (Labour / Le Travail, 1979)
This article reviews the books, "Work Without Salvation: America's Intellectuals and Industrial Alienation, 1880-1910," by James B. Gilbert, and "The Work Ethic in Industrial America 1850-1920," by Daniel T. Rodgers.

King and Context: A Reply to Whitaker - Craven, Paul (Labour / Le Travail, 1979)
Critiques Reg Whitaker's article, "Corporatism, Liberalism and Mackenzie King," published in Labour/Le Travail no. 2 (1977), in particular Whitaker's treatment of King's intellectual background and his work in labour relations prior to World War I. Revised version of a paper presented by the author at the York University conference,"Political Thought in English Canada" (1978).

Come Hell or High Water: Songs of the Buchans Miners - Frank, David (Labour / Le Travail, 1979)
This article reviews the album and book, "Come Hell or High Water: Songs of the Buchans Miners," by Breakwater Recording.

The Emergence of the Socialist Movement in the Maritimes, 1899-1916 - Frank, David; Reilly, Nolan (Labour / Le Travail, 1979)
In the years after 1899 a small but vigorous socialist movement emerged in Canada's Maritime Provinces. This article describes the origins, activities, ideas and personalities of the early socialist movement in the region. The socialists gained support in the region's industrial centres and coal-mining districts and contributed a proportionate share of the national support enjoyed by the Socialist Party of Canada and the newspaper Cotton's Weekly. The article concludes that early Canadian socialism found an important following outside western Canada and that "conservatism" is not an adequate explanation of the history of the Maritimes.

Montreal's King of Italian Labour: A Case Study of Padronism - Harney, Robert F. (Labour / Le Travail, 1979)
[The article] concerns the activities of Montreal padrone, Antonio Cordasco, who served as an intermediary between Canadian big business and Italian migrant labour during the early part of the century, in relation to the nature of padronism itself. The padrone's activities extended both along the communications network between European labour and North American industry and into many aspects of Italian life in Canada. Although the dishonesty and corruption of the padrone are clear, it is also clear that it was not the migrant labourers who objected to his work, or indeed, when it suited them, the Canadian government itself. Big business in Canada, backed by the government, needed transient labour and it was the actual immigrant policy of the Canadian government, the wish to make use of Italian labour but to prevent it from turning into permanent immigration, which made Cordasco's role possible. The migrant labourers, looking for means to make money and then return to their hometown, were happy with the padrone as long as he supplied the jobs promised them. It is shown then that the padrone came under attack only when the needs of Canadian big business did not satisfy the requirements of migrant labourers. Cordasco was destroyed, in the end, not by the Canadian government's concern for migrant labour, but by a more practical dilemma, that is, the existence of hundreds of labourers caught in Canada without work and without means of returning to their homeland.

Worker Self-Management in Industry: The West European Experience - Hunnius, Gerry (Labour / Le Travail, 1979)
This article reviews the book, "Worker Self-Management in Industry: The West European Experience," edited by G. David Garson.

Editor's Note = Note du directeur [4, May 1979] - Kealey, Gregory S. (Labour / Le Travail, 1979)
Highlights the expansion of the documents section of the journal and the inauguration of a new section on literature reviews. Invites wider contributions to the journal (poetry, fiction, theatre, musical recordings) and debates, as illustrated by Paul Craven's response in the issue to Reg Whitaker's article on Mackenzie King that was previously published in the journal. The volume is in memoriam of H.C. Pentland, whose article on the 1972 survey of the Canadian industrial relations system is published for the first time.

The Great War and Canadian Society, An Oral History - Knight, Rolf (Labour / Le Travail, 1979)
This article reviews the book, "The Great War and Canadian Society, An Oral History," edited by Daphne Read & Russell Hann.

From Trapper Boy to General Manager: A Story of Brotherly Love and Perseverance - Lunn, C. W.; McKay, Ian (Labour / Le Travail, 1979)
Introduces the life and work of journalist C.W. Lunn, including an excerpt from his serialized novel, "From Trapper Boy to General Manager." Published in the early 20th century, Lunn's portrayal of life inside the mining union in Springhill, Nova Scotia, was written with a view toward Christian self-improvement. The republication commemorates the centenary of the founding of the Nova Scotia Provincial Workmen's Association in 1879.

The Visible Hand: The Managerial Revolution In American Business - Nelles, H. V. (Labour / Le Travail, 1979)
This article reviews the book, "The Visible Hand: The Managerial Revolution In American Business," by Alfred D. Chandler, Jr.

Fools and Wise Men: The Rise and Fail of the One Big Union - Osborne, Ken (Labour / Le Travail, 1979)
This article reviews the book, "Fools and Wise Men: The Rise and Fail of the One Big Union," by David Bercuson.

Worker City, Company Town: Iron and Cotton-Worker Protest in Troy and Cohoes, New York, 1855-1884 - Palmer, Bryan D. (Labour / Le Travail, 1979)
This article reviews the book, "Worker City, Company Town: Iron and Cotton-Worker Protest in Troy and Cohoes, New York, 1855-1884," by Daniel J. Walkowitz.

The Canadian Industrial Relations System: Some Formative Factors - Pentland, H. Clare (Harry Clare) (Labour / Le Travail, 1979)
Discusses the historical development of Canadian industrial relations and compares Canada's system to the American and English. Originally written in 1972, it summarizes a number of the insights of Pentland's study for the 1968 Woods' Task Force on Industrial Relations.

H.C. (Clare) Pentland (1914-1978) - Phillips, Paul (Labour / Le Travail, 1979)
Pays homage to H.C. Pentland as a teacher and scholar who, despite the conservative intellectual climate of the Cold War, brought to the study of Canadian history a radical perspective informed by the European Marxist critical tradition. Includes photo.

The Toronto District Labour Council and Independent Political Action: Factionalism and Frustration, 1900-1921 - Piva, Michael J. (Labour / Le Travail, 1979)
This article examines the political debate within Toronto's District Labour Council (DLC) from 1900 to 1921. It argues that divisive factors within the Council hindered the emergence of an effective third party alternative in the city. The majority of the delegates to the DLC favoured the formation of a labour party controlled by trade unionists. The Council fostered the formation of such a party, but the combined opposition of left-wing delegates, who advocated affiliation with the Socialist and later the Social Democratic Parties, and right-wing delegates, who opposed third party electoral action of any kind, prevented the DLC from affiliating or working too closely with the various labour parties. During the war the socialist and labourite delegates within the Council joined forces to promote a reorganized and more broadly based Independent Labour Party, but, again, severe internal conflict prevented the ILP from winning significant electoral support in Toronto.

L'altro movimento operaio: Storia della repressione capitalistica in Germania dal 1880 a oggi - Ramirez, Bruno (Labour / Le Travail, 1979)
This article reviews the book, "L'altro movimento operaio: Storia della repressione capitalistica in Germania dal 1880 a oggi," by Karl Heinz Roth.

Natives and Newcomers: The ordering of Opportunity in Mid-Nineteenth Century Poughkeepsie - Stern, Mark J. (Labour / Le Travail, 1979)
This article reviews the book, "Natives and Newcomers: The ordering of Opportunity in Mid-Nineteenth Century Poughkeepsie," by Clyde Griffen and Sally Griffen.

The Girl of the New Day: Canadian Working Women in the 1920s - Strong-Boag, Veronica (Labour / Le Travail, 1979)
In the 1920s many liberal Canadians hoped that a modernized capitalism with new technologies and new methods of bureaucratic organization would benefit women by employment and promotion practices based on merit rather than tradition. Inequality in the workplace however, did not disappear. The failure to make great gains has sometimes been obscured by fascination with female professionals. Yet such individuals constituted a small, atypical minority. The fate of most working women lay in the non-professional employments. This study is an exploratory survey of the situation facing that majority. It begins with a brief characterization of the workforce followed by a lengthier evaluation of some of the influences which determined job selection. Career choices were basically of two types. The first, familiar blue collar occupations, were found in personal service and manufacturing. The second, in large measure, white collar, originated at the heart of the modern industrial state in the transportation and communication, commerce and finance, and clerical fields which had only relatively recently welcomed significant numbers of women. Neither choice offered women equality. The study next investigates women's collective and individual reactions to a discriminatory work situation. More exploited than their white collar sisters, blue collar workers, notably those in manufacturing, exhibited higher, more visible levels of unrest. The concluding section reviews the minimum wage legislation which, ironically enough, confirmed how little had really changed for all the anticipation of better times.

Abstracts = Résumés [v.4, 1979] (Labour / Le Travail, 1979)
English/French abstracts of articles in the issue.

Highlights of the Litterature (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Highlights of the Litterature," by Work in American Institute Inc.

Index — volume 34 — 1979 (Relations Industrielles / Industrial Relations, 1979)

Le Code de déontologie des arbitres du Québec (Relations Industrielles / Industrial Relations, 1979)
Pour le bénéfice de nos lecteurs, nous publions ici le Code de déontologie de la Conférence des arbitres du Québec qui a été adopté par cet organisme en septembre 1977.

Liste des appréciateurs 1979 / List of Referees 1979 (Relations Industrielles / Industrial Relations, 1979)

Livres reçus / Books Received (Relations Industrielles / Industrial Relations, 1979)

Livres reçus / Books Received (Relations Industrielles / Industrial Relations, 1979)

Livres reçus / Books Received (Relations Industrielles / Industrial Relations, 1979)

Livres reçus / Books Received (Relations Industrielles / Industrial Relations, 1979)

Publications récentes / Recent Publications (Relations Industrielles / Industrial Relations, 1979)

Publications récentes / Recent Publications (Relations Industrielles / Industrial Relations, 1979)

Publications récentes / Recent Publications (Relations Industrielles / Industrial Relations, 1979)

Publications récentes / Recent Publications (Relations Industrielles / Industrial Relations, 1979)

Local Union Democracy: In Search of Criteria - Anderson, John C. (Relations Industrielles / Industrial Relations, 1979)
A vast number of criteria have been proposed as indicators of union democracy. Unfortunately, little agreement exists on the relative importance of those criteria. This article examines the interrelationships between several major components of union democracy: participation, electoral control, leadership responsiveness, and union control structure. Based on the results an integrated approach to union democracy is proposed.

Injonctions et conflits du travail - Archambault, Jacques (Relations Industrielles / Industrial Relations, 1979)
Replaçant la procédure d'injonction dans son contexte sociologique en se référant aux caractéristiques essentielles du droit du travail, l'auteur préconise le rapatriement d'une procédure d'injonction modifiée dans la législation du travail et analyse les nouveaux pouvoirs accordés au Conseil canadien des relations du travail (CCRT) en matière d'ordre de ne pas faire (cease and desist order).

On Becker’s Theory of Commitment: An Empirical Verification Among Blue-Collar Workers - Baba, Vishwanath V.; Jamal, Muahammad (Relations Industrielles / Industrial Relations, 1979)
The present study attempts to assess the empirical relevance of Becker's theory of commitment to study organizational commitment among blue collar workers. The relative importance of demographic, background and job factors as possible predictors of organizational commitment are examined. The sample is drawn from packaging, power distribution and manufacturing industries in Canada. Stepwise multiple regression analysis is used to isolate the important predictors of organizational commitment.

Collective Bargaining and the Theory of Conflict - Barbash, Jack (Relations Industrielles / Industrial Relations, 1979)
The purpose of this paper is to examine conflict in the bargaining context as it operates mainly in the United States, and then draw some broad inferences for the theory of conflict.

The United States’ Withdrawal from the International Labor Organization - Beigbeder, Yves (Relations Industrielles / Industrial Relations, 1979)
After a brief description of the I.L.O., this article summarizes the main events which led to the U.S. withdrawal, reviews precedents, then tries to explain the reasons for the U.S. withdrawal and lists its consequences.

Les disparités régionales de la productivité et de la croissance au Canada ; Regional Disparities of Productivity and Growth in Canada - Bélanger, Gérard (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Les disparités régionales de la productivité et de la croissance au Canada," by L. Auer. This article reviews the book, "Regional Disparities of Productivity and Growth in Canada," by L. Auer.

Essentials of Personnal Management ; Personnel: The Management of Human Ressources - Bélanger, Laurent (Relations Industrielles / Industrial Relations, 1979)
The article reviews the books, "Essentials of Personnal Management," by Michel S. Novit, and "Personnel: The Management of Human Ressources," by Stephen P. Robbins.

Organized Behavior: an Applied Psychological Approach - Bélanger, Laurent (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Organized Behavior: an Applied Psychological Approach," by Clay Hamner & Dennis W. Organ.

La rémunération des enseignants - Belzile, Bertrand (Relations Industrielles / Industrial Relations, 1979)

Les dimensions conceptuelles du leadership et les styles qui en découlent - Bergeron, Jean-Louis (Relations Industrielles / Industrial Relations, 1979)
Après avoir proposé une définition du leadership et expliqué la différence entre dimension et style de leadership, l'auteur résume les principales études qui ont porté sur les dimensions du leadership et suggère une classification qui semble pouvoir intégrer les connaissances acquises jusqu'à maintenant. L'étude de quelques auteurs bien connus pour leurs écrits sur les styles de leadership permet ensuite de voir à quelles dimensions ces auteurs ont fait appel pour définir les styles dont ils nous parlent.

Un cadre théorique pour l’étude de la relation entre la participation et la motivation au travail - Bergeron, Jean-Louis (Relations Industrielles / Industrial Relations, 1979)
À la suite d'une description des différentes théories qui ont été avancées pour expliquer une relation possible entre la participation et la motivation, l'auteur soutient que ces théories pèchent souvent sur deux points majeurs: une définition trop vague de ce qu'est la participation et l'absence d'un modèle explicite de motivation au travail. Il s'attache donc à corriger ces déficiences et à démontrer par quels processus certaines formes de participation peuvent affecter chacune des trois composantes du modèle VIE (Expectancy) de motivation. La capacité que semble posséder ce modèle d'intégrer toutes les théories présentées au début de l'article fait ensuite l'objet d'une brève discussion.

Avis préalable de lock-out - Blouin, Rodrigue (Relations Industrielles / Industrial Relations, 1979)

Mediation, an Annotated Bibliography, by E. Levin and D.V. De Santis. - Blouin, Rodrigue (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Mediation, an Annotated Bibliography," by E. Levin & D.V. De Santis.

Labor and American Politics - Boivin, Jean (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Labor and American Politics," by Charles M. Rehmus, Doris B. McLaughlin & Frederic H. Nesbitt, Revised.

Règles du jeu et rapport de force dans les secteurs public et parapublic québécois - Boivin, Jean (Relations Industrielles / Industrial Relations, 1979)
Dans cet article, l'auteur analyse les principales modifications apportées au régime de négociation collective dans les secteurs public et para-public québécois. Après avoir affirmé que le rapport de force est au coeur même des relations du travail dans les sociétés industrielles et que la forme privilégiée que revêt l’institutionnalisation de ce rapport de force dans les pays occidentaux est la négociation collective, il s'interroge sur les conséquences de la transposition de ce mécanisme dans le secteur public. Il rappelle brièvement l'évolution historique de la négociation collective dans les secteurs public et para-public québécois et analyse la philosophie de base de la Commission créée en juillet 1977 par le gouvernement pour étudier le régime des négociations collectives en vigueur. Constatant que les principales modifications introduites par le législateur en juin 1978 s'inspirent de cette philosophie de base, il les situe par rapport aux positions exprimées par les parties syndicales et patronales devant la Commission et par rapport aux problèmes rencontrés dans les négociations antérieures.

Spirits and Demons at Work: Alcohol and Other Drugs on the Job - Boulard, René (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Spirits and Demons at Work: Alcohol and Other Drugs on the Job," by Harrison M. Trice & Paul M. Roman.

Perspectives de carrières professionnelles - Boyd, A. D.; Gross, A. C. (Relations Industrielles / Industrial Relations, 1979)
Cet article traite de l'éducation, de l'emploi et de l'utilisation de certains professionnels en contexte nord-américain.

The Ontario Labour Court 1943-1944 - Carter, Don (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "The Ontario Labour Court 1943-1944," by John A. Whilles.

Union Mergers and International Unionism in Canada - Chaison, Gary N. (Relations Industrielles / Industrial Relations, 1979)
The purpose of this paper is to highlight the difficulties en-countered in using mergers to reduce the number of unions in a country with both national and international organizations. it is seen that the presence of internationals limits the scope of potential mergers and that merger attempts can strain the relations between the Canadian sections of international unions and their parent unions.

Integrative Versus Distributive Bargaining: Choosing a Problem Resolution Process - Coleman, Rick; Fraser, C. R. P. (Relations Industrielles / Industrial Relations, 1979)
This paper examines the antithetical nature of two methods of resolving conflict through negotiation, and suggests there is an appropriate process depending upon how a party views the problem, and how he perceives it being viewed by his opponent.

Ingérence de l’employeur dans une association de salariés - Coté, André C. (Relations Industrielles / Industrial Relations, 1979)
Note sur le libellé du deuxième alinéa de l'article 24d du Code du travail du Québec.

Impact du salaire minimum sur le chômage des jeunes et des femmes au Québec - Cousineau, Jean-Michel (Relations Industrielles / Industrial Relations, 1979)
L'augmentation du salaire minimum au cours des années 70 au Québec a pu contribuer à augmenter le taux de chômage des jeunes de moins de 25 ans de 2.9 points de pourcentage et celui des femmes de 1.7 à 2.3 points de pourcentage.

Indexation des salaires et paix industrielle - Cousineau, Jean-Michel (Relations Industrielles / Industrial Relations, 1979)

Worksharing and Layoffs - Crowley, R. W. (Relations Industrielles / Industrial Relations, 1979)

L’analyse micro-économique de la hiérarchie des salaires - Daubigney, Jean-Pierre (Relations Industrielles / Industrial Relations, 1979)
L'auteur confronte la théorie micro-économique du salaire à deux problèmes de l'entreprise: la répartition de la main-d'oeuvre en groupe de salariés auxquels correspondent des classes de salaires différents et l'ampleur des disparités de rémunération entre ces catégories.

Les effectifs syndicaux québécois ou quand les chiffres dansent… - Delorme, François; Lassonde, Gaspar (Relations Industrielles / Industrial Relations, 1979)

The Social Organization of Strikes - Déom-Camiré, Esther (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "The Social Organization of Strikes," by Eric Batstone, Ian Boraston & Stephen Frenkel.

La démocratie industrielle : cogestion ou contrôle ouvrier? - Dion, Gérard (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "La démocratie industrielle : cogestion ou contrôle ouvrier?," by Dimitri Weiss.

Le fondateur du syndicalisme catholique au Québec, Mgr Lapointe - Dion, Gérard (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Le fondateur du syndicalisme catholique au Québec, Mgr Lapointe," by Robert Parisée.

Les relations du travail : Employeurs, Personnel, Syndicats, État. - Dion, Gérard (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Les relations du travail : Employeurs, Personnel, Syndicats, État," by Dimitri Weiss.

Relations du travail : Nouvelles orientations - Dion, Gérard (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Relations du travail : Nouvelles orientations," by Centre des dirigeants d’entreprise.

The Current Industrial Relations Scene in Canada 1979 ; Canadian Industrial Relations Information, Sources, Technical Notes and Glossary - Dion, Gérard (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "The Current Industrial Relations Scene in Canada 1979," by W.D. Wood & Pradeep Kumar, Edited. This article reviews the book, "Canadian Industrial Relations Information, Sources, Technical Notes and Glossary," by Pradeep Kumar.

The Role of Trade Unions in Developing Societies - Dion, Gérard (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "The Role of Trade Unions in Developing Societies," by Everett M. Kassalow & Ikanig Damachi, Edited.

Émile Gosselin 1922-1979 - Dion, Gérard; Tremblay, Marc-Adélard; Leighton, Alexander H. (Relations Industrielles / Industrial Relations, 1979)

Determinants of Officiers Militancy: The Case of the National Union of Teachers in Israël - Dolan, Shimon (Relations Industrielles / Industrial Relations, 1979)
This study reports on an empirical investigation aimed at enhancing the understanding of the ways in which personal and structural factors contribute to attitudinal militancy of officers of a national union of teachers. The study sought to assess the relationship between selected personal at tributes and selected structural characteristics in the union, and their effect on attitudinal militancy.

Specialization and Values as Inputs to Decision-Making Mining Managers - Drechsler, Herbert d; Frost, Peter J.; Barnowe, J. Thad; Chafetz, Israël (Relations Industrielles / Industrial Relations, 1979)
This thrust of this paper is to explore the objectives which mining managers perceive as important for effective organizational functioning in terms of their values, of the sense they make of the world around them in two specific, fundamental areas, orientation toward people and toward things, and of the interaction between managerial values and this orientation.

L’effet du salaire minimum sur les prix, l’emploi et la répartition des revenus : le cas du Québec - Fortin, Pierre (Relations Industrielles / Industrial Relations, 1979)
Les principales conclusions de cet article sont qu'un niveau élevé du salaire minimum, sans poser d'obstacle insurmontable quant à la stabilité des prix dans une économie aussi exposée à la concurrence extérieure que l'économie du Québec, risque de soutenir un niveau de chômage plus important qu'on a pu le croire jusqu'à ce jour, et tout spécialement parmi les jeunes; et que le salaire minimum élevé est un moyen très inefficace de mieux répartir les revenus qu'il vaudrait mieux remplacer par des outils d'intervention mieux appropriés comme un régime de revenu familial garanti ou même des plans de soutien du revenu un peu plus modestes.

Grievance Initiation and Resolution. A Test of the Behavioural Theory - Gandz, Jeffrey (Relations Industrielles / Industrial Relations, 1979)
The Author puts Walton and McKersie's behavioural theory of labour negotiations to test in a study of a non-random sample of 118 bargaining units.

Formation-emploi des diplômés en relations industrielles. Une étude de cas : Université de Montréal - Guérin, GIlles (Relations Industrielles / Industrial Relations, 1979)
Dans une perspective d'ajustement des programmes de formation aux exigences professionnelles du marché du travail en relations industrielles, cet article analyse les résultats d'une enquête faite par questionnaire en mai 1978 auprès de la population des diplômés en relations industrielles de l'Université de Montréal.

The Legality of Picketing - Handman, Suzanne; Leopold, John (Relations Industrielles / Industrial Relations, 1979)
The authors attempt, by means of « jurisprudence » to determine the conditions and circumstances which render picketing legal or illegal. Within this context, picketing will be examined from the point of view of object, form and occasion. In addition, the sanction of picketing will be presented, followed by a critique of the subject.

Employment Problems of the Native People in Ontario - Jain, Harish C. (Relations Industrielles / Industrial Relations, 1979)

Employees’ Participation in Management: International Experiences and the Prospects for Canada - Jecchinis, Chris A. (Relations Industrielles / Industrial Relations, 1979)
The experiences of certain successful West European practices in employee's participation within undertaking recommend the establishment of complementary institutional arrangements in the existing system of labour-management relations in Canada which, at the present, is based only on the institution of collective bargaining.

H.C. Pentland and Working Class Studies - Kealey, Gregory S. (Canadian Journal of Political and Social Theory, 1979)
Analyzes Pentland's pathbreaking contributions to Canadian history and political economy.

Collective Bargaining and Conflict Resolution in Education : The Evolution of Public Policy in Ontario - Kervin, John B. (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Collective Bargaining and Conflict Resolution in Education : The Evolution of Public Policy in Ontario," by Bryan M. Downie.

Final Offer Arbitration. A Comment - Lacombe, Trefflé (Relations Industrielles / Industrial Relations, 1979)

Gestion des ressources humaines. Une approche systémique - Larouche, Viateur (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Gestion des ressources humaines. Une approche systémique," by Laurent Bélanger.

La dimension interculturelle dans la gestion du personnel et l’ACDI - Lortie, Pierre (Relations Industrielles / Industrial Relations, 1979)

The Effect of Changes in Minimum Wage Rates on Provincial Unemployment Rates, 1970-77 - Maki, Dennis R. (Relations Industrielles / Industrial Relations, 1979)
This paper estimates the effect of different minimum wage to average wage ratios among provinces on differences in provincial unemployment rates. The effect is found to be statistically significant, but small in magnitude.

Taille des établissements et taux de rémunération au Québec - Marion, G.; Lacroix, R.; Latraverse, S. (Relations Industrielles / Industrial Relations, 1979)
Les auteurs analysent l’effet de la taille des établissements sur les taux de rémunération pour 5 551 établissements du Québec. Ils concluent que ces effets sont importants pour les salariés du secteur de la production, mais sont limités pour les cols blancs.

Une analyse des gains au Canada - Marion, Gérard (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Une analyse des gains au Canada," by Peter Kuch et Walter Haessel.

Labour Hoarding and the Wage Share: Test of a Hypothesis - Marion, Gérard; Spencer, Byron G. (Relations Industrielles / Industrial Relations, 1979)
The authors seek to build on the work of Bail and St. Cyr, Smith and Ireland, Solow, and others, in order to estimate the assessment of labour hoarding and test the relationship between labour hoarding and the wage share.

Labor and Politics in Spain Today - Martin, Benjamin (Relations Industrielles / Industrial Relations, 1979)
The trade unions elections of 1977 in Spain conferred a formal end of four decades of labour authoritarianism and marked the second major electoral process that has been established for the re-establishment of democratic institutions. According to the author, the outcome has important implications for the emerging national political configuration, the restructuring of the labour-management relationship, and the political strategies of the major political parties.

Décisions rendues par le CRTC - Martineau, Luc (Relations Industrielles / Industrial Relations, 1979)
Le Conseil a accueilli une requête en révision présentée par le Syndicat canadien des télécommunications transmarines (SCTT) en vertu de l'article 119 du Code qui demandait d'ajouter à l'unité de négociation existante un groupe considérable d'employés exerçant des fonctions comparables à celles du premier groupe mais dont les qualifications techniques étaient plus exigeantes. Constatant que la requête ne modifiait pas la nature, l'essence et la portée inten- tionnelle de l'unité de négociation existante et d'autre part, que le syndicat requérant a pu démontrer qu 'il était désiré par une majorité globale des employés dans l'unité, le Conseil a décidé d'ajouter les employés visés par ladite requête, sauf une restric- tion à l'égard des professionnels, sans tenir compte de leur dési

Die Polnishe Diskussion un die Arbeiterräte / Polish Discussion on the Works councils - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Die Polnishe Diskussion [um] die Arbeiterräte = Polish Discussion on the Works Councils [The Polish Debate on Workers' Councils]," by Viktoria Grevemeyer-Korb.

Industrial Democracy in Western Europe, A North American Perspective - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Industrial Democracy in Western Europe, A North American Perspective," by John Crispo.

Socio-Political Implications of Job Reform - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1979)
The author examines the job reform movements developing in various parts of the world, but particularly in the democratic developed societies, may have in the long any substantial socio-political impact.

Using the Social Sciences - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Using the Social Sciences," by Albert Cherns.

Retour sur le régime caché d’assistance-sociale - Mercier, Jacques (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Retour sur le régime caché d’assistance-sociale," by Rapport du Conseil canadien du bien-être social.

Salaire et marché du travail à l’entreprise - Mercier, Jacques (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Salaire et marché du travail à l’entreprise," by Jean-Pierre D’Aubigney.

Salaire et marché du travail interne à l’entreprise - Mercier, Jacques (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Salaire et marché du travail interne à l’entreprise," by Jean-Pierre d’Aubigney.

Measuring Absenteeism - Mikalachki, A.; Gandz, Jeffrey (Relations Industrielles / Industrial Relations, 1979)
The purpose of this paper is twofold: to provide a rationale for expending effort on measuring absenteeism and to unravel some of the complexities associated with the measurement and interpretation of absenteeism data.

When Workers Fight : The Politics of Industrial Relations in the Progressive Era - Miller, Sally M. (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "When Workers Fight : The Politics of Industrial Relations in the Progressive Era," by Bruno Ramirez.

Managers as Consumers of Organizational Behavior: An Historical Perspective on the « Relevance » Debate - Moore, Larry F.; Pinder, Craig C. (Relations Industrielles / Industrial Relations, 1979)

Determinants of Weekly Work Hours in Canada - Newton, Keith; Leckie, Norm (Relations Industrielles / Industrial Relations, 1979)
This paper is an attempt to shed some empirical light on the underlying determinants of the length of the work week.

Multinational Union Activity in the Paper Industry - Northrup, Herbert R.; Rowan, Richard L. (Relations Industrielles / Industrial Relations, 1979)
After considering the many attempts of cooperation among unions in multinational firms particularly the paper industry, the authors are not optimistic about results in the immediate future.

L’évolution des emplois et de la main-d’oeuvre dans l’industrie automobile - O’Farrell, Kevin (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "L’évolution des emplois et de la main-d’oeuvre dans l’industrie automobile," by Centre d’étude et de recherches sur les qualifications.

The Western Canadian Labour Movement, 1897-1919 - Pentland, H. Clare (Harry Clare) (Canadian Journal of Political and Social Theory, 1979)
The objective of this essay is to establish and clarify the dimensions, the character, and the significance of the remarkable labour movement that developed in western Canada in the closing decades of the nineteenth century and flourished during the great boom of the early twentieth century. Within this general purpose are some particular ones: to demonstrate the rapidity of the numerical growth of unionism in the West, to suggest some reasons for it, and to show why western unionists were far more radical and militant than eastern ones. –Introduction
Keywords: Pentland; critical theory; cultural studies; economics; philosophy; political science; sociology

Rational/Statistical Method of Test Validation - Pinder, Craig C. (Relations Industrielles / Industrial Relations, 1979)
This study demonstrates the application of a test validation procedure similar to that described by Mobley and Ramsay (1973) but which avoids the use of factor analysis in isolating dimensions upon which subsequent job subgrouping is based. Instead, a semi-judgmental, semi-statistical method was employed. Actual test validation data are reported which, although missing in Mobley and Ramsay's (1973) article, attest to the utility of a job grouping approach to the validation problem.

Collective Bargaining Attitudes of Registered Nurses in the United States and Canada: A Wisconsin-Ontario Comparison - Ponak, Allen; Haridas, T. P. (Relations Industrielles / Industrial Relations, 1979)
This paper compares the attitudes to collective bargaining of a sample of Ontario and Wisconsin registered nurses. Contrary to expectations (in view of the general low rate of American nursing unionism), the Wisconsin nurses who where surveyed viewed collective bargaining at least as favourably as their Ontario counterparts.

Absenteeism and Labour Turnover in Selected Ontario Industries - Robertson, Gordon (Relations Industrielles / Industrial Relations, 1979)
The primary objective of this survey is therefore to collect enough data to in order that comparisons of absenteeism and labour turnover can be made within various regions and industries in Ontario. The study also provides general information on the extent, nature and relative importance of various human problems.

L’indexation des salaires dans les pays industrialisés à économie de marché - Rondeau, Claude (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "L’indexation des salaires dans les pays industrialisés à économie de marché," by Bureau international du travail.

Union Maids: Organized Women Workers in Vancouver 1900-1915 - Rosenthal, Star (BC Studies: The British Columbian Quarterly, 1979)
The history of women in the labour force is by and large a neglected area of study, especially with regard to trade unionism. For British Columbia in the early years of this century, while there are various accounts of men's union struggles, there does not exist at present any published secondary material on the union activity of women. This article will attempt to give a preliminary account of the organization of some women workers in Vancouver during the period from 1900 to 1915. –Introduction

Grievance Arbitration of Discharge Cases, A Study of the Concept of Industrial Dsicipline and their Result - Roy, André (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Grievance Arbitration of Discharge Cases, A Study of the Concept of Industrial Dsicipline and their Result," by George W. Adams.

L’obligation d’obéir et ses limites dans la jurisprudence arbitrale québécoise - Roy, André (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "L’obligation d’obéir et ses limites dans la jurisprudence arbitrale québécoise," by C. D’Aoust & G. Trudeau.

Labour Supply Implications of a Negative Income Tax Plan - Roy, Arun S. (Relations Industrielles / Industrial Relations, 1979)
This study demonstrates that a Negative Income Tax Plan can be expected to result in fairly large reductions in the supply of work effort in the case of younger workers. The potential reductions in labour supply of female workers appear to be particularly large.

CETA: Manpower Programs Under Local Control - Sexton, Jean (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "CETA: Manpower Programs Under Local Control," by William Mirengoff & Lester Rindler.

Characterization of Canadian Strikes: Some Critical Comments - Smith, Michael R. (Relations Industrielles / Industrial Relations, 1979)
This paper examines examples of two different intellectual traditions within which Canadian strikes are interpreted. The distinctiveness of the two traditions becomes most clear in reactions to a paper by Crispo and Arthurs (1968) on industrial conflict in the mid i960*s. Each tradition involves assumptions about the nature of industrial conflict. In neither of the examples discussed from the two traditions, however, is the adequacy of the assumptions really established. Despite the fact that these two traditions assert entirely contradictory characterizations of Canadian strikes, there appears to be no serious dialogue between the exponents of either position.

Effects of Wage and Price Controls in Canada : 1975-1978 - Staudohar, Paul D. (Relations Industrielles / Industrial Relations, 1979)
The author examines the recent Canadian experience in wage and price controls» including an analysis of these controls, the problems confronting their implementation, and certain of their results.

Les normes internationales du travail - Tran Van, Kim Chi (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Les normes internationales du travail," by Bureau international du travail.

L’application du droit du travail provincial à l’entreprise construisant des pistes d’atterrissage à Mirabel - Tremblay, Guy Gérard (Relations Industrielles / Industrial Relations, 1979)

La formation matérielle de la classe ouvrière à Montréal entre 1790 et 1830 - Tremblay, Robert (Revue d'histoire de l'Amérique française, 1979)
À la lumière des récents travaux sur le mouvement ouvrier au Québec, nous en sommes venus à constater la nécessité de mettre en relief les mécanismes de formation de la classe ouvrière. Plus précisément, nous avons posé les questions, à savoir: quels ont été les premiers modes d'appropriation de la force de travail par le capital? Comment s'est tissé un premier réseau de rapports de production capitalistes à l'intérieur de l'espace colonial que représente le Bas-Canada au début du XIXe siècle? Dans la poursuite de cet objectif, nous avons utilisé une documentation comprenant plus de 3 000 actes notariés (surtout des contrats d'engagement et un nombre moindre de conventions de marché)2 de façon à dégager le mieux possible les traits dominants de l'organisation du travail à Montréal entre 1790 et 1830. –Introduction

La réforme des lois du travail - Veilleux, Diane (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "La réforme des lois du travail," by neuvième colloque des relations industrielles.

La participation à une grève illégale en tant que motif de congédiement - Verge, Pierre (Relations Industrielles / Industrial Relations, 1979)
Le congédiement d'un salarié au seul motif de sa participation à une grève illégale contredit-il le maintien légal du lien de salariat à la suite d'une grève? Comment l'envisager en regard de la protection de l'activité syndicale? S'agit-il de deux questions distinctes ou, ou contraire, d'une même réalité? La prise de position récente de la Cour d'Appel à ce sujet, à la suite de jugements parfois divergents du Tribunal du travail, est d'autant plus importante que le Code du travail prétend maintenant assurer expressément aux salariés le recouvrement de leur emploi à la suite d'une grève.

La solidarité syndicale devant un piquet de grève - Verge, Pierre (Relations Industrielles / Industrial Relations, 1979)
Les dispositions « anti-briseurs de grève » du Code du travail ont-elles modifié la détermination de la légalité d'un piquet de grève? Concrètement, l'association accréditée serait-elle maintenant habilitée à s'assurer de l'efficacité de l'arrêt de travail? Par ailleurs, quelles sont les conséquences juridiques du refus de travailler, par solidarité syndicale, de salariés se rattachant à des unités de négociations non visées par la grève?

Accroissement de la productivité et psychologie du travail - Vinet, Alain (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Accroissement de la productivité et psychologie du travail," by Éditions de l’Université de Bruxelles.

S’adapter à un monde en pleine évolution. Choix de textes sur la qualité de la vie au travail - Vinet, Alain (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "S’adapter à un monde en pleine évolution. Choix de textes sur la qualité de la vie au travail," by George F. Sanderson, Edited.

Santé et sécurité au travail - Vinet, Alain (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Santé et sécurité au travail," by Gouvernement du Québec.

International Labour Law Reports - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "International Labour Law Reports," by Zvi H. Bar-Niv, Benjamin Aaron, Thilo Ramm, Fokle Schmidt, Jean Maurice Verdier, Kenneth William Wedderburn, Peter Elman, Alphen ann den Rijn, Sijthoff & Noordhoff, Edited.

La Contrattazione colletiva in Italia (1945-1977) ; Democrazia politica e democrazia industriale - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "La Contrattazione colletiva in Italia (1945-1977)," by Bruno Veneziani, Edited. This article reviews the book, "Democrazia politica e democrazia industriale," by Silvana Sciarra.

Le phénomène syndical - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Le phénomène syndical," by Patrick de Laubier.

Women and the Making of the Working Class: Lyon, 1830-1870 - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "Women and the Making of the Working Class: Lyon, 1830-1870," by Laura S. Strumingher.

The Saskatchwan Government’s Internal Arrangements to Accomodate Collective Bargaining - Wetzel, Kurt; Gallagher, Daniel G. (Relations Industrielles / Industrial Relations, 1979)
This study looks at three models employee! by Saskatchewan's provincial public sector management to facilitate bargaining. First is a relatively conventional adaptation to bargaining with provincial civil servants. In the second, associations of nursing homes and hospitals bargain in the presence of a government observer. The third has the government and school trustees, with government holding the balance of power, negotiating jointly with the teachers. The paper also discusses the central coordination and control functions which the government has developed to deal with bargaining.